International Graduate Outcomes in the United Kingdom - Stern, Vivienne (International Higher Education, 2019)
The United Kingdom’s International Education Strategy sets a target to attract 600,000 international students by 2030, an increase of 30 percent. With Brexit, there is a sharper awareness across government of the benefits that international students and graduates confer in economic terms and in long-term positive influence on perceptions of the United Kingdom itself. To reach this target, the country needs to offer opportunities for international graduates to remain in the United Kingdom and work for a period post graduation. It also needs to understand, and where possible improve upon, the strength of its offer to prospective international students.